The combined analysis of urine and blood metabolomics profiles provides an accurate prediction of the training and competitive status of Chinese professional swimmers - Yang, R.; Wang, Y.; Yuan, C.; Shen, X.; Cai, M.; Wang, L.; Hu, J.; Song, H.; Wang, H.; Zhang, L. (Frontiers in Physiology, 2023)
Objective: The purpose of this study was to employ metabolomics for the analysis of urine metabolites in swimmers, with the aim of establishing models for assessing their athletic status and competitive potential. Furthermore, the study sought to compare the identification efficacy of multi-component (urine and blood) model versus single-component (urine or blood) models, in order to determine the optimal approach for evaluating training and competitive status.